Electrolyte Physiology Of Selected Serum Electrolytes And Nitric Oxide In Preeclamptics At The Korle-Bu Teaching Hospital - Darkwa, E.O (My University, 2016)
Brief Background: Preeclampsia is a multisystem disorder in pregnancy affecting 5-14% of all pregnancies worldwide. Preeclampsia is associated with an increased risk of cardiovascular diseases later in life of both the mother and the baby. It is common but its aetiology remains unknown. It is the most common, yet least understood disorder of pregnancy. Despite a steady reduction in maternal mortality from this disorder in more developed countries, the aetiology still remains unclear, recent studies indicate that serum electrolytes and Nitric oxide (NO) levels may play a role in pre-eclampsia since it is vascular endothelial disorder. Magnesium and nitric oxide play important role in peripheral vasodilatation whiles calcium also have an indirect effect on smooth muscle function by increasing magnesium levels. However, the levels of these electrolytes and NO in normal pregnancy and preeclampsia patients are still uncertain. The aim of this study is to measure serum levels of calcium and magnesium in preeclamptic pregnancy and to compare with those in normal pregnancy. Aim: To determine the electrolyte physiology of selected serum electrolytes and nitric oxide in preeclamptics at the Korle-Bu Teaching Hospital. Brief Methodology: This was a case-control cross sectional study involving 162 women consisting of 30 preeclamptics, 100 normotensive pregnant women and 32 normotensive non-pregnant women conducted at the Obstetrics and Gynaecology clinic of Korle-Bu Teaching Hospital. Women in each of these categories were sampled consecutively and recruited into the study after obtaining an informed consent. Preeclampsia was diagnosed using the International Society for the Study of Hypertension in Pregnancy criteria. Blood pressure and heart rate of the participants were measured after which 5 ml of venous blood was obtained from each participant. Blood pressure was measured using a mercury sphygmomanometer and a stethoscope. Heart rate was determined by auscultation with a stethoscope and a stopwatch. Determination of serum magnesium and calcium was done using a Flame Atomic Absorption Spectrometer (Variant 240FS manufactured by VARIAN Australia Pty Ltd). Serum sodium and potassium were analysed using Sherwood Flame Photometer (Model 420 by Sherwood Scientific Ltd). Nitric oxide was measured using Griess reagent system by ELISA method (Promega, Madison, USA). Results: The study showed a statistically significant difference in the serum levels of magnesium, sodium and potassium in normotensive non-pregnant women (0.80±0.10, 139.16±4.64, 3.61±0.51), normotensive pregnant (0.77±0.14, 139.00±6.54, 3.75±0.47) and preeclamptic women (0.70±0.15, 136.13±4.17, 3.45±0.54) mmol/L (p=0.006, p=0.009, p=0.009) respectively. There was no statistically significant difference in the serum levels of calcium (total and ionised) and nitric oxide in normotensive non-pregnant (2.20±0.16, 1.19±0.09, 470.5), normotensive pregnant (2.14±0.34, 1.20±0.11, 1308.3) and preeclamptic (2.13±0.30, 1.15±0.06, 1178.78) women (p=0.564, p=0.091, p=0.447) respectively. Conclusion: This study revealed abnormalities of some selected serum electrolytes which may have a role in the pathophysiology of preeclampsia. This is evidenced by the finding of a significantly reduced serum magnesium, sodium and potassium levels in preeclampsia compared to normotensive pregnant women. However, no change was found in the serum levels of calcium (total and ionised) and nitric oxide levels in preeclampsia compared to normotensive pregnant women.
Thesis (MPhil)
Keywords: Electrolyte Physiology; Serum Electrolytes; Nitric Oxide; Preeclamptics; The Korle-Bu Teaching Hospital; Ghana